Dampak Perceraian Orangtua terhadap Psikologis Remaja - Nazla Meyvida; Izma Aulia Rachmat; Lestari Amelia; Sri Mulyeni (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
Divorce is the legal and religious termination of a husband-wife relationship. This severance of the relationship can have psychological consequences, making children more susceptible to depression. These psychological impacts include deep sadness, resulting in depression, feelings of loss, shame, anger, disappointment, denial, self-acceptance, and feelings of blame toward the parents. These psychological impacts are naturally the result of the support, emotional support, and presence of the parents before, during, and after the divorce. This study employed a qualitative research method with a phenomenological approach, conducted through semi-structured interviews. The aim is to raise awareness among readers that divorce not only impacts the husband and wife but also the psychological impact on children, which is often considered unimportant. However, the mental health of children after divorce is a crucial issue that requires attention. This is where the role of parents is crucial in shaping their character and psychological development. This study concludes that children who are victims of divorce tend to seek out activities outside the home, as the integrity of their home is no longer there. Children experience sadness and loss most acutely. Furthermore, children are more wary of future relationships due to a loss of trust in the meaning of romantic relationships. Low self-acceptance also makes it difficult for children to control their emotions.